Profiles and correlates of language and social communication differences among young autistic children - Reetzke, Rachel; Singh, Vini; Hong, Ji Su; Holingue, Calliope B.; Kalb, Luther G.; Ludwig, Natasha N.; Menon, Deepa; Pfeiffer, Danika L.; Landa, Rebecca J. (Frontiers in Psychology, 2022)
Delays in early language development are characteristic of young autistic children, and one of the most recognizable first concerns that motivate parents to seek a diagnostic evaluation for their child. Although early language abilities are one of the strongest predictors of long-term outcomes, there is still much to be understood about the role of language impairment in the heterogeneous phenotypic presentation of autism. Using a person-centered, Latent Profile Analysis, we first aimed to identify distinct patterns of language and social communication ability in a clinic-based sample of 498 autistic children, ranging in age from 18 to 60 months (M=33 mo, SD=12 mo). Next, a multinomial logistic regression analysis was implemented to examine sociodemographic and child-based developmental differences among the identified language and social communication profiles. Three clinically meaningful profiles were identified from parent-rated and clinician-administered measures: Profile 1 (48% of the sample) “Relatively Low Language and Social Communication Abilities,” Profile 2 (34% of the sample) “Relatively Elevated Language and Social Communication Abilities,” and Profile 3 (18% of the sample) “Informant Discrepant Language and Relatively Elevated Social Communication Abilities.” Overall, young autistic children from the lowest-resource households exhibited the lowest language and social communication abilities, and the lowest nonverbal problem-solving and fine-motor skills, along with more features of attention-deficit/hyperactivity disorder and atypical auditory processing. These findings highlight the need for effective community-based implementation strategies for young autistic children from low-resource households and underrepresented communities to improve access to individualized quality care.